The Situation of Cadmium Contamination in Rice from the Main Areas of Rice Cultivation in 4 Regions of Thailand - Sakolkittinapakul, Jakkit; Benjapong, Wenika (Thai Journal of Toxicology, 2021)
Rice can absorb cadmium and accumulate in grain. High levels of cadmium in rice grain can affect human health and trade. This study aims to assess the situation of cadmium contamination in Thai rice. Rice samples were collected from rice mills and rice distributors located in the main areas of rice cultivation in four regions of Thailand (58 provinces) during 2013–2014. Cadmium contents in 420 rice samples were determined by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The cadmium concentrations in the rice samples ranged from below the detection limit to 0.375 mg/kg. No sample exceeded the maximum limit for cadmium in rice according to Codex and Thai food standard (0.4 mg/kg). No significant difference was observed in cadmium content between polished rice and unpolished rice. Average cadmium content in glutinous rice was higher than that of non-glutinous rice. The mean cadmium concentrations in polished Hom Mali, unpolished Hom Mali, polished mixed cultivars, unpolished mixed cultivars, unpolished colored rice, polished white glutinous rice and unpolished colored glutinous rice were 0.026, 0.025, 0.018, 0.021, 0.021, 0.032 and 0.034 mg/kg, respectively. Rice samples collected from different regions contained different cadmium levels. The estimated cadmium exposure from rice consumption of Thai population was well below the Provisional Tolerable Monthly Intake (PTMI). It indicates that Thai rice samples contain low cadmium levels that do not impact on consumer health. However, the monitoring needs to be focused in rice grown in cadmium-contaminated areas.